2021
DOI: 10.1186/s12917-021-02781-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fasting plasma insulin and proxy measurements to assess insulin sensitivity in horses

Abstract: Background Proxies are mathematical calculations based on fasting glucose and/or insulin concentrations developed to allow prediction of insulin sensitivity (IS) and β-cell response. These proxies have not been evaluated in horses with insulin dysregulation. The first objective of this study was to evaluate how fasting insulin (FI) and proxies for IS (1/Insulin, reciprocal of the square root of insulin (RISQI) and the quantitative insulin sensitivity check index (QUICKI)) and β-cell response (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Firstly, the outcome used to establish the cut-off must be considered. Some studies relied on diagnostic tests, such as the euglycemic hyperinsulinaemic clamp (EHC) [35] or combined glucose-insulin test (CGIT) [36], to detect insulin-resistant horses, while others were conducted prospectively, with laminitis as an outcome [37][38][39]. Another study reported a confidence interval for basal insulin in healthy ponies [41].…”
Section: Comparison Of Cut-off Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the outcome used to establish the cut-off must be considered. Some studies relied on diagnostic tests, such as the euglycemic hyperinsulinaemic clamp (EHC) [35] or combined glucose-insulin test (CGIT) [36], to detect insulin-resistant horses, while others were conducted prospectively, with laminitis as an outcome [37][38][39]. Another study reported a confidence interval for basal insulin in healthy ponies [41].…”
Section: Comparison Of Cut-off Valuesmentioning
confidence: 99%
“…Despite all these differences, the published cut-offs for basal insulin values with laminitis as an outcome averaged at around 30 µIU/mL once converted to the Mercodia Equine assay [37][38][39]. The cut-offs targeting insulin resistance or ID were lower at around 10 to 20 µIU/mL (once converted) [34][35][36]41]. This is unsurprising, as the likelihood of laminitis incidence is correlated with the degree of hyperinsulinaemia, meaning that slightly insulin-resistant horses may not develop laminitis at all, even though they remain at risk.…”
Section: Comparison Of Cut-off Valuesmentioning
confidence: 99%